Artificial Diiron Enzymes with a De Novo Designed Four‐Helix Bundle Structure. Issue 21 (28th July 2015) - Chino, Marco; Maglio, Ornella; Nastri, Flavia; Pavone, Vincenzo; DeGrado, William F.; Lombardi, Angela
Abstract: Invited for the cover of this issue is the group of Angela Lombardi at the University of Napoli "Federico II", Italy. The cover image shows a construction site where workers are building up a four‐helix bundle scaffold. Fine‐tuning of the metal binding site, which is the heart of the construction, enables a specific function, such as oxidative chemistry. This approach has been successfully employed to develop diiron–oxo protein models. Abstract : The road to construct molecules that function as environmentally safe catalysts and biosensing devices is now open... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 3371 ff .